2004
DOI: 10.4028/www.scientific.net/msf.449-452.637
|View full text |Cite
|
Sign up to set email alerts
|

Model for the Protective Oxidation of Mg-Ca Alloys Containing Be at Elevated Temperature

Abstract: The liquid oxidation behavior of Mg-Ca base alloys containing Be has been presented in this paper. The ignition temperature test and microbalance measurement indicated that the oxide film formed at elevated temperature was protective, resulting in the improved oxidation resistance and ignition-proof properties. A Ca-rich zone was found at the very near surface of oxide layer. With Be addition the oxide layer became dense and compact, which was impermeable for the rapid diffusion of oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Choi et al [19] found that increasing Ca content, in the range 0.3-5 wt%, increased the ignition temperature of AZ91 and that Be, in the range 0.002-0.005 wt.%, further increased the ignition resistance. Huang et al [20] produced similar results for pure Mg containing Ca and Be.…”
Section: Introductionmentioning
confidence: 66%
“…Likewise, Choi et al [19] found that increasing Ca content, in the range 0.3-5 wt%, increased the ignition temperature of AZ91 and that Be, in the range 0.002-0.005 wt.%, further increased the ignition resistance. Huang et al [20] produced similar results for pure Mg containing Ca and Be.…”
Section: Introductionmentioning
confidence: 66%